Efeito tripanocida dos ácidos betulínico e oleanóico - Sousa, Paloma Leão (2017)
Chagas disease is a neglected disease caused by the parasite Trypanosoma c ruzi and is a public health problem world wide . Current treatment is restricted by the frequent side effects and limited efficacy of benznidazole . Betulinic acid (BA) and oleanolic acid (OA) are triterpenes found in several medicinal plants and exhibit a wi de variety of biological and pharmacological activities, including an effect on trypanosomatids. The objective of the present study was to evaluate the trypanocidal effect and mechanism of action of betulinic and oleanolic acids on Trypanosoma cruzi strain Y in vitro . Antiproliferative activity of BA and OA (1.56 200  M) were evaluated during 24, 48 and 72 hours on epimastigote, trypomastigote and amastigote forms of T. cruzi . Viability of LLCMK2 cell s , treated with BA and OA (200 1600  M), was evaluated for 24 h using the MTT assay. The mechanism of action assays were performed on the epimastigote form s treated with IC50 of BA and OA, incubated for 24 h, then labeled with annexin V/7AAD, Rho123, H2DCFDA, Acridine Orange and MDC according to the manufacturer's instructions and analyzed by flow cytometry and confocal mic roscopy. Data were analyzed using ANOVA with Bonferroni post test or Student ’s t test, * p 0.05. BA inhibited the growth of epimastigotes after 24h (I C 50 = 73.43  M; BZ = 21 8  M), 48h (I C 50 = 119.8  M; BZ = 61  M) and 72h (I C 50 = 212 2  M; BZ = 16.5  M) of incubation and i nhibited the viability of trypomastig otes (I C 50 = 51 88  M; BZ = 257  M) after 24 h. OA inhibited the growth of epimastigote s after 24 h (IC50 = 11.66  M, BZ = 218  M), 48 h (IC50 = 43.15  M, BZ = 61  M), and 72 h IC50 = 43.05  M; BZ = 16.5  M ) of incubation and i n hibited the viability of trypomastigotes (IC50 = 13.97 μ M; BZ = 257  M) after 24 h. BA and OA decreased the percentage of infected cells and reduced the number of amastigotes per cell 24h and 48h after treatments, respectively. Both terpenes showed no toxicity on LLCMK2 cells at the concentrations used in trypanocidal tests. The analysis of cell death mechanism of the BA treated parasite s showed alterations in mitochondrial membrane potential, changes in cell membrane integrity, increased formation of reactive oxygen species and detection of acidic compartments. The treatment with OA demonstrated the detection of acidic compartments and autophagic vacuoles. Our results demonstrate that BA and OA have a trypanocidal effect on all evolutionary forms of T. cruzi Y strain, suggesting that the BA mechanism of cell death occurs through necrosis and that of the OA through autophagy in epimastigote forms.